Implementasi Sistem Informasi Ujian Online Berbasis Web Pada Sekolah Alam Al-Karim - Rahmatulloh, Bagus Sifak Udin; Ahmad, Imam (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
In the world of education, exams are a form of evaluation of the learning process in order to measure the level of achievement of skills, character and intelligence of students, thus making exams an important stage in the teaching and learning process. In the application of technological advances Al-Karim natural school uses google classroom technology to improve the efficiency and accessibility of exams. However, limited features that are not available in google classroom are a problem in conducting exams. Such as the lack of effectiveness, efficiency, and security in the exam implementation process. This problem requires a large and potentially dangerous system. This paper presents the implementation of a customized web-based online exam information system for Al-Karim natural school using the Moodle learning management system (LMS). The proposed system aims to simplify the exam process, offering benefits such as effectiveness, efficiency, and enhanced security. learning management system (LMS) development as an online learning platform that uses the Moodle platform. The research method used is research and development (RD), and the development model includes potential and problems, data collection, product design, product trial, and report. The research tool is a questionnaire used by teachers and students. Results from beta testing the research tool showed that 98,8% of learning media strongly agreed with this application. Initial feedback from stakeholders showed positive acceptance, with users appreciating the system's intuitive interface and convenience. However, ongoing monitoring and evaluation is essential to address potential issues and further optimize system performance.